Medicalization and Pharmaceuticalization- A Recent Concern - Jha, Kunal; Singh, Arpita; J. , Avinash; Barman, Diplina; Agrawal, Pratik (International Journal of Psychosocial Rehabilitation, 2020)
Medicalization is a process through which non-medical tribulations are converted to as medical problems, generally in stipulations of illnesses or disorders. Medicalization engines includes: clients, bio-technology and superintended care. Improved research and theoretical mirroring on medicalization has recommended analogous concepts resembling biomedicalization, Pharmaceuticalization and genetization. Medicalization has evoked controvercies within social sciences, that contemplates on extending the medicine’s jurisdiction and its role over human bodies by reducing the social phenomena to individual biological pathologies. There is an increased concern towards extention of the pharmaceutical marketing unswerving both doctors and other healthcare professionals. The role of patients during this economy has also changed. Patients were regarded as passive sufferers of medicalization earlier but now are advocates, regulars, or even representatives of change. In Dentistry, it has been reported that due to the inaccessibility of curative procedures patients are more likely to indulge in “self- medication” or misuse of “pharmaceuticalization”. The topic justifies the aspects a Public health Dentist should explore to improve the oral health conditions of the population.